Herbal Tea of Torbangun Leaf and Exclusive Breastfeeding: Related Factors and Impact on the Duration of Breastfeeding - Pakpahan, Sulastry; Panggabean, Hetty (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Exclusive breastfeeding is a critical intervention in reducing infant mortality and addressing issues related to nutritional status. Utilizing lactagogues is one approach to enhance the secretion and production of breast milk. Torbangun leaves (Coleus amboinicus l.) contain phytochemical components such as alkaloids, sterols, triterpenoids, tannins, and flavonoids, which are known to enhance breast milk production, increase milk protein concentration, accelerate ovulation, improve protein digestion, and aid in breast milk production. This study aims to assess the efficacy of torbangun leaf herbal tea in influencing the duration and frequency of breastfeeding in the North Tapanuli Regency. The study included a sample size of 64 participants meeting the inclusion criteria, divided into treatment and control groups through purposive sampling. Data collection involved interviews using questionnaires and was analyzed using Chi-Square and One-Way ANOVA at a significance level of ? = 5%. The findings revealed that maternal knowledge (p-value 0.010.05) and a history of early initiation of breastfeeding (EIBF/IMD) (p-value 0.080.05) were significantly associated with exclusive breastfeeding. A higher level of knowledge was associated with a 3.7-fold greater likelihood of achieving successful exclusive breastfeeding, while early initiation of breastfeeding increased the chances by 4.19 times. One Way ANOVA results demonstrated that the duration and frequency of breastfeeding were notably higher and more significant among mothers who used torbangun leaf herbal tea compared to those who did not (p0.05). Recommendations include the following: 1) Increasing maternal awareness regarding the significance of exclusive breastfeeding and the use of torbangun plants to support breast milk production. 2) Promoting active engagement by healthcare professionals in disseminating information about the importance of exclusive breastfeeding and the utilization of herbal plants to enhance the success of exclusive breastfeeding.